2021
DOI: 10.3390/biomedicines9121915
|View full text |Cite
|
Sign up to set email alerts
|

Metabolic Fatty Liver Disease in Children: A Growing Public Health Problem

Abstract: Metabolic-associated fatty liver disease (MAFLD), previously called nonalcoholic fatty liver diseases (NAFLD), is one of the most important causes of chronic liver disease worldwide and will likely become the leading cause of end-stage liver disease in the decades ahead. MAFLD covers a continuum of liver diseases from fatty liver to nonalcoholic steatohepatitis (NASH), liver fibrosis/cirrhosis and hepatocellular cancer. Importantly, the growing incidence of overweight and obesity in childhood, 4% in 1975 to 18… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
15
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 25 publications
(26 citation statements)
references
References 89 publications
1
15
0
1
Order By: Relevance
“…Despite the efforts done by several scientific research groups, there are currently no effective pharmacologic therapies and subsequently no current clinical practice guidelines' recommendations, regarding the medications/ supplementations used in the treatment of pediatric NAFLD (4,6). Weight loss and increased physical activity through lifestyle modification and a well-balanced diet still remains the mainstay of pediatric NAFLD management (4,6,24). The results of our study denote that probiotics might have a beneficial effect in the treatment of pediatric NAFLD by decreasing liver transaminases' levels and by improving individual parameters of the metabolic syndrome.…”
Section: Discussionmentioning
confidence: 99%
“…Despite the efforts done by several scientific research groups, there are currently no effective pharmacologic therapies and subsequently no current clinical practice guidelines' recommendations, regarding the medications/ supplementations used in the treatment of pediatric NAFLD (4,6). Weight loss and increased physical activity through lifestyle modification and a well-balanced diet still remains the mainstay of pediatric NAFLD management (4,6,24). The results of our study denote that probiotics might have a beneficial effect in the treatment of pediatric NAFLD by decreasing liver transaminases' levels and by improving individual parameters of the metabolic syndrome.…”
Section: Discussionmentioning
confidence: 99%
“…The nephrotic state is associated with hyperlipidemia 20 and obesity is generally a worrying problem in children and adolescents worldwide. 38,39 Kirpalani et al 20 observed increased MPA CL/F values along with lower albumin concentrations and haematocrit as well as higher triglycerides and cholesterol. We found a few correlations between the cholesterol and the pharmacokinetic and pharmacodynamic parameters as well as higher cholesterol in younger children.…”
Section: Discussionmentioning
confidence: 98%
“…High calories, carbohydrates, and fat increase the prevalence of chronic diseases associated with insulin resistance, such as NAFLD [25,38,40]. The increased consumption of sweetened beverages, particularly among children and adolescents, leads to increased fructose adsorption with increased lipogenesis, triglycerides accumulation, and liver damage due to its metabolism [41]. Moreover, macronutrient composition in the diet can impact the incidence of these chronic diseases without affecting body weight [38].…”
Section: Discussionmentioning
confidence: 99%